O processo de comunicação interna e as barreiras à eficácia comunicativa: estudo de agências do Instituto Brasileiro de Geografia e Estatísticas (IBGE) do sertão da Paraíba - Moraes, Louise de Oliveira Soares (Universidade Federal Rural do Semi-Árido, 2018)
In the current Era marked by the value of information, communication has received prominence, especially in the organizational environment. Communicating accurately can be instrumental in ensuring the smooth running of a business and for achieving goals and results more or less effectively. In the context of the Public Administration, although communicative impasses are more specific, resulting from the bureaucratic structure, the transmission of information also plays a determining role. Thus, trying to understand the influence of the communicative element in this scope, the present work had as objective to analyze the process of internal communication in a public organ of the Sertão paraibano. For this, the following specific objectives were defined: to understand how the internal communication occurs in the agencies of the Brazilian Institute of Geography and Statistics (IBGE) studied; identify the most used means of communication, analyze interpersonal relationships. In addition, we sought to identify if workers are aware of the importance of the importance of communication to achieve results and the barriers / failures in internal communication. The sample of this study was composed of 20 employees, distributed among the IBGE agencies located in Sousa / PB and Pombal / PB, in the Sertão region of Paraíba. The research was based on quantitative and qualitative methods, guided by the authors' approaches and had a descriptive character. The results suggest that workers understand the importance of internal communication in the agencies and points to a positive relationship between the levels, but factors such as the high turnover of contractors and the difficulty of expressing opinions do not favor the dissemination of information in an environment in which the dialogue is the main communication channel. In addition, bottom-up communication has also stood out as a point to be worked on, because although they know some internal barriers, employees are hesitant to give suggestions for improving the process. The IBGE's integrated communication policy also showed itself as a strong potential to be developed.
Monografia
Keywords: Comunicação interna; Falhas na comunicação; Barreiras comunicativas; Comunicação no setor público; Internal communication; Communicative barriers; Communication in the public sector; Communication failures; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO